'… again to breathe fully from two lungs': Eastern Catholic Encounters with History and Ecclesiology. Issue 4 (October 2016) - O'Mahony, Anthony
The Eastern Catholic churches have a distinct history and ecclesiology; which is the consequence of often being located on the frontier between Western and Eastern Christianity. The 23 Eastern Catholic churches represent a unique oecumene of theological, spiritual and linguistic traditions and cultures - Armenian, Coptic, Ethiopic, Syriac and Byzantine. These traditions are little known despite their continuing significance and importance. The Russian poet and scholar Vjaceslav Ivanov (1866-1949) created the concept that the Christian Church needed to '…again to breathe fully from two lungs'. This paper engages with certain aspects of the history and ecclesiology of the Eastern Catholic churches in the context of modern Europe.